Identifying Sarcopenia in Female Long‐Term Care Residents: A Comparison of Current Guidelines. Issue 2 (20th November 2017) - Kotlarczyk, Mary P.; Perera, Subashan; Nace, David A.; Resnick, Neil M.; Greenspan, Susan L.
Abstract : Objectives: To establish the prevalence of sarcopenia in a long‐term care population, assess agreement among different consensus sarcopenia diagnostic criteria, and examine agreement of a self‐reported questionnaire with consensus guidelines. Design: Cross‐sectional secondary analysis. Setting: Long‐term care communities in the greater Pittsburgh, Pennsylvania, area. Participants: Women aged 65 and older (mean 83.6) undergoing eligibility screening for a fracture reduction trial (N = 141). Measurements: We measured appendicular lean muscle mass using dual‐energy X‐ray absorptiometry. Hand grip strength and usual gait speed were also evaluated. Sarcopenia status was determined according to European Working Group on Sarcopenia in Older People (EWGSOP) and the Foundation for the National Institutes of Health (FNIH) Sarcopenia Project criteria and the SARC‐F questionnaire. Results: Eleven participants were sarcopenic (7.8%) according to the EWGSOP criteria, six (4.3%) according to FNIH conservative cut‐point guidelines, and 32.6% (n = 46) according to FNIH intermediate cut‐points. Only 2 of 141 participants met criteria for sarcopenia according to all three guidelines. Sarcopenia was identified in 30 (21.3%) participants according to the SARC‐F questionnaire. Sensitivity of the SARC‐F with consensus panel definitions ranged from 18.2% to 33.3%. Specificity ranged from 78.7% to 81.1%. Conclusion: Current consensus criteria from the EWGSOP and FNIH Sarcopenia Project do not agree and have little overlap in older female long‐term care residents. The SARC‐F questionnaire is a simple tool that could be implemented in long‐term care, but it has low sensitivity compared with current consensus guidelines in the identification of sarcopenic individuals.